Proceedings of COMPCON '94
DOI: 10.1109/cmpcon.1994.282943
|View full text |Cite
|
Sign up to set email alerts
|

The Scalable Coherent Interface: scaling to high-performance systems

Abstract: With the ANSIAEEE Std 1596-1 992 Scalable Coherent Interface (SCI), a few or many processors can share cached data in a coherent fashion (i.e. their caches are transparent to software). Scalability constrains the protocols to rely on simple request-response protocols, rather than the eavesdrop or 3-party transactions assumed by (unscalable) bus-based systems.The linear nature of the base SCI protocols limits their performance when data is being actively shared by large numbers of processors. To meet these need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…-First, the model could be enlarged to cover the full set cache coherence protocol and all of the processor/cache options defined in the SCI Standard. Furthermore, the extensions of the SCI cache coherence protocol currently under development (for an overview see [10]) could be included in the model. -Second, in the current version of our model, the processor/cache options have to be enabled/disabled by hand and they are identical for all nodes.…”
Section: Future Workmentioning
confidence: 99%
“…-First, the model could be enlarged to cover the full set cache coherence protocol and all of the processor/cache options defined in the SCI Standard. Furthermore, the extensions of the SCI cache coherence protocol currently under development (for an overview see [10]) could be included in the model. -Second, in the current version of our model, the processor/cache options have to be enabled/disabled by hand and they are identical for all nodes.…”
Section: Future Workmentioning
confidence: 99%
“…This protocol is an IEEE standard (Std 1596(Std -1992. "The SCI coherence protocols are based on a distributed directories scheme [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, for data-acquisition purposes, commercially available SCI products are very rare, and for high-end applications nothing is provided since this market segment is too small. A lot of research remains to be done in this field [8][9][10][11][12]17]. In this paper, the performances of two SCI tests stands are reported that show the principal suitability of SCI for data-acquisition systems in future fusion reactor experiments.…”
Section: Introductionmentioning
confidence: 99%